The Effectiveness of Animation Media on The Language Skills of Class V Students - Sidabutar, Yanti Arasi; Manihuruk, Leonita Maria Efipanias; Adelberth, Carles (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research aims to see the effectiveness of animation media on the language skills of class V students at SDN 091537 Pematangsiantar. This research will be carried out in class V at SD Negeri 091537 Hutabayu which is located at Hutabayu Village, Hutabayuraja District, Simalungun Regency. This research was carried out in the odd semester of the 2023/2024 academic year. The population in this study were all fifth grade students at SD Negeri 091537 Hutabayu. In this study, the population was all fifth grade students at SD Negeri 091537 with a total of 25 students. Data analysis techniques in quantitative research use statistics, namely parametric statistics and the data analyzed is in the form of a ratio scale or interval scale. Data is taken from a normally distributed population. This research discusses whether audio-visual media is effective in improving students' speaking abilities. In this research, an experimental method was used using an initial test (pretest) and final text (posttest). From the t-test paired samples test above, a t-value of 14.713 can be obtained with a significance level of 0.000. Because the significant probability is much smaller than 0.05, namely 0.000 and tcount is 14.713 > ttable = 2.05183, then Ho is rejected. H1 is accepted. This shows that there is effectiveness of animation media on the language skills of class V students at SDN 091537 Pematangsiantar.